Studies in Asymmetric Epoxidation of Chalcone Using Quaternary Salts and Nonionic Surfactants Based on 6-Amino-6-deoxy-glucose as Chiral Phase Transfer Catalysts - Lalit Sharma; Subhash Chander Sharma; Saroj (E-Journal of Chemistry)
Quaternary salts and nonionic surfactants based on 6-amino-6-deoxy-glucose were explored as chiral phase transfer catalysts for the asymmetric epoxidation of chalcone. Quaternary salts used in the present study, were void of any branched chain or long hydrocarbon chain, whereas the sugar based nonionic surfactants have a long hexadecyl moiety as tail. It was observed that quaternary salts showed no activity as phase transfer catalysts but sugar based nonionic surfactants acted as chiral phase transfer catalysts. It was also revealed that hydrophilicity of the surfactant favors more yield whereas stereochemistry governs enantioselectivity. (6,6'-Hexadecylimino) bis(6-deoxy-1,2-O-isopropylidene-α-D-glucofuranose) was found to be the most suitable chiral phase transfer catalyst, resulting asymmetric epoxidation of chalcone with 90% yield and 16.5% enantiomeric excess (ee).